Fresno County Bar Association Law Day Luncheon with Robert McConnell - Watkins, Howard::::::::: (1984)
William Ninnis holding Fresno County Voluntary Legal Services Pro Bono Award presented by Howard Watkins Howard headed the Fresno County Voluntary Legal Services Program for Fresno-Merced Counties Legal Services